ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, NET OPERATING MARGIN, FINANCING TO DEPOSIT RATIO, NON PERFORMING FINANCING DAN PEMBIAYAAN BAGI HASIL TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA (Studi Kasus Bank Umum Syariah di Indonesia Tahun 2011-2015) - Sari, Silfani Permata; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2017)
The purpose of this research is to examine the effects of Capital Adequacy Ratio, Net Operating Margin, Financing to Deposit Ratio, Non Performing Financing, and Profit Sharing toward profitability of Sharia Commercial Banks of 2011-2015 period. The writer used the data from Quarterly Publication Financial Reports of Sharia Commercial Banks of 2011-2015 period.The populations of the research were 11 Sharia Commercial Banks in Indonesia. However, after passing the purposive sampling stage, there were only 5 samples of Sharia Commercial Banks that were feasible to be investigated, which were Bank Mandiri Syariah, Bank Central Asia Syariah, Bank Rakyat Indonesia Syariah, Bank Muamalat Indonesia, and Bank Negara Indonesia Syariah. The analitical technic that the writer used in this research was multiple linear regression which purpose was to obtain the whole image of the relation among variables. Classical assumption test that the writer used in this research were multicollinearity test, autocorrelation test, heteroscedasticity test, and normality test.The result of this research shows that CAR variable affects negatively and significantly toward ROA. NOM variable affects positively and non-significantly toward ROA. NPF variable affects negatively and significantly toward ROA. Meanwhile, FDR variable affect negatively and non-sicnificantlu and Profit Sharing affect positively and significantly toward ROA. The prediction ability of the five variables toward ROA is 26,5%, while the rest is affected by other factors that are not investigated in this research.